Efektivitas Minyak Atsiri Serai Untuk Pengendalian Penyakit Mosaik Kacang Panjang - Supyani Supyani; Salim Widono; Ulfaizah Ulfaizah (Agrosains : Jurnal Penelitian Agronomi, 2017)
Production of cowpea has declined, one of them caused by virus infection that caused mosaic disease which was still difficult to controlled. This study aimed to determine the effectivity of antiviral compounds on lemongrass essential oils to development of mosaic disease and the relationship to growth and development of cowpea that infected. This study used Completely Randomized Design (CRD) with two factors, they are the time of application and concentration of lemongrass essential oil. Data were analyzed using F test and DMRT at level of 5%. Results showed that application of lemongrass essential oil at concentration of 1,8% before planting (soaking seeds) tend to delaying the emergence of mosaic disease symptoms. Application of lemongrass essential oil at all of concentration that used, can inhibiting the disease intensity up to 31.39%. However, apllication of lemongrass essential oils in plants infected with a virus that causes mosaic has not able to improve plant growth and development.